2012
DOI: 10.1111/1574-6968.12011
|View full text |Cite
|
Sign up to set email alerts
|

Beware of proteins bearing gifts: protein antibiotics that use iron as a Trojan horse

Abstract: Multicellular organisms limit the availability of free iron to prevent the utilization of this essential nutrient by microbial pathogens. As such, bacterial pathogens possess a variety of mechanisms for obtaining iron from their hosts, including a number of examples of vertebrate pathogens that obtain iron directly from host proteins. Recently, two novel members of the colicin M bacteriocin family were discovered in Pectobacterium that suggest that this phytopathogen possesses such a system. These bacteriocins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Specialized receptors then transport siderophore-iron complexes back into the cell. Some antimicrobials, including sideromycins, pyocins, and bacteriocins, use siderophore receptors to access intracellular targets (3134), and we hypothesized that TS may use this strategy. We compared P. aeruginosa PAO1 grown in 10:90 with increasing concentrations of TS alone ( Fig 3A ) or with 0.1μM EDDHA, a membrane-impermeable iron chelator (35) ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Specialized receptors then transport siderophore-iron complexes back into the cell. Some antimicrobials, including sideromycins, pyocins, and bacteriocins, use siderophore receptors to access intracellular targets (3134), and we hypothesized that TS may use this strategy. We compared P. aeruginosa PAO1 grown in 10:90 with increasing concentrations of TS alone ( Fig 3A ) or with 0.1μM EDDHA, a membrane-impermeable iron chelator (35) ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…The narrow range of specificity of the second antibiotic, agrocin 434 (Rhizobium rhizogenes), is also consistent with a Trojan horse function, although its full chemical structure and mode of action are unknown. Several other narrow specificity Trojan horse antibiotics that involve a toxic component and a second component for high-efficiency delivery into target cells have now been identified in other bacterial species and have been investigated to develop synthetic, narrow-spectrum, high-activity antibiotics for human medicine (Grinter et al 2013;Rebuffat 2012).…”
Section: The Search For Biocontrol Agentsmentioning
confidence: 99%
“…We recently described the novel M-class bacteriocins pectocin M1 and M2, which are produced by and active against strains of the soft-rot phytopathogens Pectobacterium atrosepticum (Pba) and Pectobacterium carotovorum (Pbc) (Grinter et al ., 2012a; 2013 , ). The domain structure of these proteins suggested that they challenge the dogma that an IUTD is the universal mechanism by which colicin-like bacteriocins achieve translocation.…”
Section: Introductionmentioning
confidence: 98%